A 78-Year-Old Female with a Diffuse Pruritic Rash and Palmoplantar Desquamation - Gabriel E. Molina; Melissa J. Danesh; Ruth K. Foreman; Daniela Kroshinsky (MDPI AG, 2020)
Mycosis fungoides, the most common cutaneous T-cell lymphoma, is known to exhibit varied clinical presentations and mimic many other dermatoses. This morphological heterogeneity can often lead to initial misdiagnoses resulting in significant delays from symptom onset to diagnosis. We report a case of mycosis fungoides imitating clinical and histopathological features of erythema annulare centrifugum.